Perancangan dan Implementasi Sistem Informasi Geografis Wisata Kota Purwodadi Berbasis Mobile - Gilang Fahri; Migunani Migunani (JURNAL TEKNIK INFORMATIKA DAN MULTIMEDIA, 2022)
An abstranct is a brief summary of a In the search for a location, requires a position in the delivery of geographic information from a tourist attraction. Currently the most widely known online map is Google Maps which can be accessed easily via Android Mobile with the help of internet technology. Therefore, by utilizing these technologies, it is expected to produce a mobile application that can make it easier for tourists to find the desired tourist attractions, especially in Purwodadi City. However, there are obstacles in finding tourist attractions, especially for tourists from outside Purwodadi City. Information about tourism in Purwodadi still uses a lot of print media, while the delivery of information in print media can be said to be less effective because it requires a lot of resources, for example, the use of excessive paper. And people who are interested usually first look for information from the internet. The information sought is usually about Purwodadi attractions, Purwodadi City News, Purwodadi city history, gift shops and hotels in Purwodadi city. Along with the development of increasingly advanced technology, the use of the internet can be done anywhere, either through a computer or a mobile device so that the information needed can be accessed quickly. Moreover, by using a mobile device we can access information anywhere because it is easy to carry anywhereally as an overview of what appears in the paper.